PELAKSANAAN EVALUASI PEMBELAJARAN MELALUI PENILAIAN HARIAN PADA ANAK USIA DINI - Siti Khodijah Lubis; Ratno Susanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Implementing learning evaluation through daily assessment at RA Yahdina has used the child development achievement scale, anecdotal notes, and records of children's work, but the implementation has not been maximized. Therefore, this study aims to describe the implementation of learning evaluation through daily assessment in early childhood at RA Yahdina through qualitative research methods. Data collection uses interviews and documentation, and data analysis is done through descriptive qualitative study. The results showed that the daily assessment at RA Yahdina using a developmental achievement scale only assessed aspects of religious, language, and cognitive development. In contrast, other aspects of development did not exist. Then the implementation of anecdotal notes is carried out on monthly assessments, even though this technique must also be done on daily assessments. Meanwhile, records of children's work already contain aspects that are assessed against children's work